VINE VARIETIES FOR WHITE WINES IN THE CLIMATE CONTEXT OF THE ODOBESTI VINEYARD, ROMANIA - Ionica BOSOI; Liliana ROTARU; Marioara PUȘCALĂU; Cintia COLIBABA (Journal of Applied Life Sciences and Environment)
Odobeşti Vineyard is one of the most famous and oldest Romanian vineyards, with a focus on white wines. To improve the existing assortment of varieties over time at the Research and Development Station for Viticulture and Vinification, Odobesti (RDSVV, Odobești), four vine varieties were obtained and approved: ʹŞarbaʹ (1972), ʹBăbească griʹ (1975), ʹMioriţaʹ (1980) and ʹVranceaʹ (2018), with superior quality and productive potential and a high capacity to capitalise on the edaphoclimatic conditions specific to this viticultual area. This study presents the behaviour of these varieties of vines in the climatic conditions of the Odobesti Vineyard in the period 2017–2021. The following parameters were studied and determined: the phenological spectrum of the vine, fertility and productivity (% fertile shoots, fertility coefficients, productivity indices), quantity and quality of grape production (grapes/vine, average bunch weight, grape production/vine, sugar content, total acidity and glucoacidimetric index). The data obtained were compared with the ʹSauvignon Blancʹ variety, which is widely grown in this area. The evolution of the vegetation phenophases was conditioned by the climatic factors during the study period. There was a tendency to shorten them due to the increase in air temperature values. The variety ʹVranceaʹ presented a high fertility potential (89.5% fertile shoots), the varieties ʹBăbească griʹ and ʹMiorițaʹ showed a higher productive potential than the control variety ʹSauvignon Blancʹ (6.06–6.12 kg/vine), and the variety ʹȘarbaʹ recorded the highest accumulations in sugars (230.5 g/L). In the climatic context of the Odobești Vineyard, the white wine varieties ʹȘarbaʹ, ʹBăbeasca griʹ, ʹMiorițaʹ and ʹVranceaʹ have demonstrated a valuable agrobiological and technological potential, comparable to that of the ʹSauvignon Blancʹ variety.